2012
DOI: 10.5850/jksct.2012.36.4.422
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study on the Purchase Timing Effect in Athletic Shoes -Focused on Day-of-the-week Effect and Intra-month Effect-

Abstract: The influence of a marketing mix on the consumer purchasing process is well documented in academic fields; however, studies of when consumers purchase fashion brands or products in terms of the day-ofthe-week effect and 10-days-of-the-month effect on various channels to a given brand in practice are limited in the fashion industry. This study empirically describes the purchase timing behavior for athletic shoes using daily sales data from a domestic brand in Korea from January in 2006 to December in 2010. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…BIC refers to a difference in maximum likelihood values between the observation and the measurement model, thus a smaller value is regarded to have higher explanation power. In other words, two equations with the same form as equation (7), hiding in this observation, are shown as one equation in the whole market. In analyzing the sample with two segmented markets, the explanation power of observation increased to 0.679.…”
Section: Deduction Of a Model Coefficient For The Segmented Marketmentioning
confidence: 85%
See 4 more Smart Citations
“…BIC refers to a difference in maximum likelihood values between the observation and the measurement model, thus a smaller value is regarded to have higher explanation power. In other words, two equations with the same form as equation (7), hiding in this observation, are shown as one equation in the whole market. In analyzing the sample with two segmented markets, the explanation power of observation increased to 0.679.…”
Section: Deduction Of a Model Coefficient For The Segmented Marketmentioning
confidence: 85%
“…Kwak (2015) reported that the delivery amounts before those holidays was greater than during ordinary days, and decreased after those holidays. Additionally, Lee, et al, (2012) reported that there is a day of the week effect on agricultural products and prices. Therefore, this study developed a model with the holiday effect and the day of the week effect added to the basic model of equation ( 6).…”
Section: Modification Of the Model Considering The Nature Of Agricultural Product Datamentioning
confidence: 99%
See 3 more Smart Citations